(untitled) (Belmont, California, 1998)
Custom edition (probably UTEP). Preface and Chapters 1-14 from American Government and Politics Today, with appendices A, B, C, glossary & index. From Introduction to Texas Politics, 6e, chapters 1-8, appendix, and index
Keywords: Political parties,Political science; United States